Public Awareness regarding Common Eye Diseases among Saudi Adults in Riyadh City: A Quantitative Study - Waleed A. Al Rashed; Amro K. Bin Abdulrahman; Ahmed A. Zarban; Mohammed S. Almasri; Abdulrahman S. Mirza; Rajiv Khandekar (Journal of Ophthalmology)
Aim. The current study aimed to evaluate the knowledge of eye disease and awareness of eye care among the Saudi adults and to explore existing eye-related misconceptions in the community. Methods. A cross-sectional study was conducted in Riyadh city during May and June 2016. A self-administered anonymous online questionnaire was used to explore the most common misconceptions related to eye diseases and eye care. Results. Out of 1000 individuals, only 711 (71.1%) participant responses were received. The participants’ acceptable knowledge (score ≥50%) was high about the eye problem in diabetes (88.6%), ocular trauma (81.2%), and other general eye diseases (91.3%), whereas low about refractive errors (63%), pediatric eye problems (51.5%), and glaucoma (14.8%). The variation in knowledge about specific ocular morbidities was significant (p<0.001). The majority of participants reported sources of information about the common eye diseases and eye care encountered from the community, internet-based resources, and social media. Conclusions. The majority of the participants had awareness about the common eye diseases, whereas low percentage of participant’s awareness about specific condition of eye diseases. Public eye health awareness should be more focused on social media and the internet to be able to cover the younger individuals of the community.